Hubungan Pemberian Makanan Pendamping ASI Dengan Kejadian Stunting Pada Balita Di Wilayah Kerja Puskesmas Belakang Padang Kota Batam - Resi Novia (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Stunting is a crhonic malnutrition problem caused by low nutrition intake. the prevalence of stunting in the District of Belakang Padang in 2020 is quite high 16.8% compared to the average of Batam City which is 7.21%. This study aims to determine the correlation between complementary feeding and the incidence of stunting in toddlers in the working area of the Puskesmas Belakang Padang, Batam City. This observational research use case control design on the toddlers years who are in Belakang Padang. The sampling technique is done by using purposive sampling with a sample of 36 subjects in each group. Data analysis was performed on univariate analysis and bivariate analysis using chi-square test with CI = 95%, significant level (Î± = 0,05).Statistical test result showed that complementary feeding have a significant relation with incidence of stunting (p = 0,005) and odd ratio 0,249. It is hoped that health services should increase the provision of information and education to mothers of toddlers about the importance of nutrition and the correct way of processing complementary feeding needed by toddlers in an effort to prevent stunting.